PENGARUH CITRA MEREK, KUALITAS LAYANAN, PROMOSI DAN HARGA TERHADAP MINAT BELI KEMBALI JASA ANTAR OJEK ONLINE MEREK GRAB-BIKE DI JAKARTA PUSAT - Jesse Juliet (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2020)
Komisi Pengawas Persaingan Usaha (KPPU) stated that Go-Jek won a market share in Indonesia's ride-hailing industry which reached almost 80 percent, while Grab's market share was only 14.69% plus UBER which had been acquired at 6.11%, so Grab's market share is only 20.8%. From this problem, the authors are interested in studying what factors influence the way Grab controls the market share by analyzing the Grab-Bike brand image factors that have been communicated so far, service quality needs, consistency in providing and informing promos, and the suitability to repeat buying intention by using Grab-Bike service. The object of this research is the Grab company with Grab-Bike online motorcycle taxi services. The sample of this study is customers who have used Grab-Bike services located in Central Jakarta. The sampling technique used in this research is judgment sampling. Sample collected by distributing questionnaires using google form with a total of 104 respondents. Data analysis techniques to test each variables SPSS 20. Based on the results of this study it is known that the value of validity is greater than the value of table R (> 0.1927), the value of reliability is greater than 0.60. The results of the model significance test (F test) are 0.000 (<Î± 0.05), coefficient significance test (t-test) from service quality, promotion, and the price is lower than Î± 0.05, test coefficient of determination (test R2) 0.660. This study has the result that service quality, promotion, and price have a positive significant influence on the interest in buying back Grab-Bike motorcycle taxi services in Central Jakarta, but the brand image is not. Keywords: Brand image, service quality, promotion, price, repeat buying intention.